Cardiac Failure as an Unusual Presentation in a Patient with History of Amyotrophic Lateral Sclerosis - Mohammad Hasan Namazi; Isa Khaheshi; Habib Haybar; Shooka Esmaeeli (Case Reports in Neurological Medicine)
Amyotrophic lateral sclerosis (ALS) is the most well-known form of motor neuron diseases in which both upper and lower motor neurons are involved in this disease. We presented an unusual case of ALS whom had presented with chief complaint of dyspnea. Cardiac failure was diagnosed at the final stage of the ALS disease. The pathogenetic mechanism leading to an elevated occurrence of cardiomyopathy in ALS is not comprehensible. Dilated cardiomyopathy has been explained in some previous studies. Based on the collected data, it was hypothesized that cardiomyopathy is underdiagnosed in the ALS population, probably because symptoms are masqueraded as a result of the patients’ disability. It was suggested that in all motor neuron diseases a serial cardiological evaluation should be executed, including annual echocardiography.